The Tolerance of Several Hybrid Corn (Zea mays L.) Varieties Type on Cob Rot in the Plateau of Simalungun Regency (International Journal of Scientific Research and Management (IJSRM), 2020)
The research was carried out in Dolog Masagal Subdistrict, Simalungun Regency, altitude ± 1.100 m above sea level. The research was conducted from January to May 2019. The purpose of this study was to determine the tolerance level of several hybrid corn varieties to cob rot disease. Methods for conducting the research used randomized block design (RBD) with 1 factor. Types of hybrid corn varieties tested were: Pioneer 29 (V1), NK 99 (V2), Pioneer 12 (V3), NK 22 (V4), Pioneer 4 (V5), Nusantara I (V6), Asia 1 (V7).The parameters observed were: plant height, cob diameter, cob length containing seeds, number of seed rows per cob, number of seeds per row, number of seeds per cob, husk cover in cob, cob rot intensity, the amount of dry production per plot, and the weight of 1.000 seeds. Based on the research results, different types of hybrid corn varieties produce different tolerances of cob rot resistance in the Simalungun highlands. The most tolerant variety of cob rot disease is Pioneer 29 (mild damage scale = 0 - 10%). Different types of varieties planted also affect various components of growth and production, among others: plant height, number of seeds per row, number of seed rows per cob, husk cover on cob, dry production per plot, and weight of 100 grains. As for the parameters of cob diameter, cob length containing seeds and the number of seed rows per cob, the difference in varieties did not significantly affect.